ln(x-3)-2=8

Simple and best practice solution for ln(x-3)-2=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-3)-2=8 equation:


Simplifying
ln(x + -3) + -2 = 8

Reorder the terms:
ln(-3 + x) + -2 = 8
(-3 * ln + x * ln) + -2 = 8
(-3ln + lnx) + -2 = 8

Reorder the terms:
-2 + -3ln + lnx = 8

Solving
-2 + -3ln + lnx = 8

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + -3ln + 2 + lnx = 8 + 2

Reorder the terms:
-2 + 2 + -3ln + lnx = 8 + 2

Combine like terms: -2 + 2 = 0
0 + -3ln + lnx = 8 + 2
-3ln + lnx = 8 + 2

Combine like terms: 8 + 2 = 10
-3ln + lnx = 10

Reorder the terms:
-10 + -3ln + lnx = 10 + -10

Combine like terms: 10 + -10 = 0
-10 + -3ln + lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 2+(-5)=x | | 2(x+4)-16=20 | | 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= | | 2+x=-(x+6) | | 2(13x-15)+3(x-19)=0 | | 2x+5+3x=15 | | h+4=-3 | | -4(3y-6)-y=-3(y-4) |

Equations solver categories